Nongenomic Androgen Activation of Phosphatidylinositol 3-Kinase/Akt Signaling Pathway in MC3T3-E1 Osteoblasts - Hong‐Yo Kang; Chung-Lung Cho; Kai-Lieh Huang; Jyh-Chwan Wang; Yueh‐Chiang Hu; Hui‐Kuan Lin; Chawnshang Chang; Ko-En Huang (2004)
Androgens have important effects on the bone metabolism. However, the effect and mechanism of androgen action on the osteoblasts remains unknown. Here we showed that androgens increase phosphorylation and nuclear translocation of Akt. siRNA-AR prevented androgen-induced Akt activation in MC3T3-E1 cells. This suggests that nongenomic androgen activation of Akt is mediated by androgen receptor in osteoblasts.Androgens have important effects on the human skeleton in both males and females. However, the mechanism of androgen action on bone metabolism remains unknown. The aims of this study were to determine the effect and mechanism of androgen action on the osteoblast cells.Here we showed that 5alpha-dihydrotestosterone (DHT) accelerates cell growth of the MC3T3-E1 cell line in a time- and dose-dependent manner. The specific phosphatidylinositol 3-kinase (PI 3-kinase) inhibitor LY294002 and kinase-deficient Akt mutant can repress the androgen effect on MC3T3-E1 cells. Western blot analysis showed that DHT, 17beta-estradiol, and testosterone (T) induce a rapid and transient phosphorylation of Akt in MC3T3-E1 cells. This activation reached to a plateau after 15 minutes and gradually diminished after 60 minutes of DHT treatment.Fluorescence microscopy showed a distinct increase in immunostaining intensity in the nuclear interior after androgen treatment but no change in the subcellular distribution of Akt when the cells were pretreated with hydroxyflutamide (HF) or LY294002. In addition, small interfering RNA against androgen receptor (siRNA-AR) prevented DHT-induced Akt phosphorylation and cell growth.These findings represents the first physiological finding to indicate how steroid hormones such as androgens can mediate the nuclear localization of Akt/PKB in osteoblasts that has previously mainly been linked to growth factor-induced events occurring at the plasma membrane level.